2018
DOI: 10.1016/j.expneurol.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Single severe traumatic brain injury produces progressive pathology with ongoing contralateral white matter damage one year after injury

Abstract: There is increasing recognition that traumatic brain injury (TBI) may initiate long-term neurodegenerative processes, particularly chronic traumatic encephalopathy. However, insight into the mechanisms transforming an initial biomechanical injury into a neurodegenerative process remain elusive, partly as a consequence of the paucity of informative pre-clinical models. This study shows the functional, whole brain imaging and neuropathological consequences at up to one year survival from single severe TBI by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 71 publications
12
77
0
1
Order By: Relevance
“…Multiple regions have been implicated, however timing at intervals on the order of multiple seconds, is strongly linked to the frontal cortex and its motor output via the basal ganglia [37, 38]. Given the ongoing and progressive nature of brain damage, these circuits and their white matter connections may continue to degrade over time [39]. While this was not addressed in the current study, investigation of these pathological changes and associated behavioral aberrations at later time points would be of great benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple regions have been implicated, however timing at intervals on the order of multiple seconds, is strongly linked to the frontal cortex and its motor output via the basal ganglia [37, 38]. Given the ongoing and progressive nature of brain damage, these circuits and their white matter connections may continue to degrade over time [39]. While this was not addressed in the current study, investigation of these pathological changes and associated behavioral aberrations at later time points would be of great benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse hippocampal lesion model, depletion of microglia by 30-day treatment with a CSF1R inhibitor, PLX3397, improved functional recovery and reduced pro-inflammatory gene expression in hippocampus (Rice et al, 2015). Despite evidence that chronic evolving microglial activation is detrimental following moderate-severe TBI (Byrnes et al, 2012;Loane et al, 2014;Pischiutta et al, 2018), prolonged inhibition of microglia is unlikely to be therapeutic because microglia perform critical functions such as synaptic pruning and restoration of tissue homeostasis after pathological insult (Salter and Stevens, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Male B6.129S4(Cg)-Mapt tm1(EGFP)Klt /J, referred to as tau knock-out (KO) mice, were from Jackson Laboratory (#029219, USA) 36 Mouse model of TBI. The controlled cortical impact brain injury mouse model used in this study replicates both the mechanical forces and the main secondary injury processes observed in severe TBI patients with brain contusion and gives clinically-relevant behavioral and histopathological outcomes 14,37 . WT and tau KO mice were anesthetized by isoflurane inhalation (induction 3%; maintenance 1.5%) in an N2O/O2 (70%/30%) mixture and placed in a stereotaxic frame.…”
Section: Methodsmentioning
confidence: 99%